Evaluation of the transverse aortic constriction model in ICR and C57BL/6J mice - Huang, Mengying; Yu, Lishuang; Wang, Xiaoping; Wang, Mingmin; Li, Weili; Tang, Jiayang; Ling, Guanjing; Wei, Xiaoqi; Wang, Yong; Wang, Wei; Wu, Yan; Lu, Linghui (Frontiers in Physiology, 2022)
Transverse aortic constriction (TAC) is a frequently used model to investigate pressure overload-induced progressive heart failure (HF); however, there is considerable phenotypic variation among different mouse strains and even sub-strains. Moreover, less is known about the TAC model in ICR mice. Therefore, to determine the suitability of the ICR strain for TAC-induced HF research, we compared the effects of TAC on ICR and C57BL/6J mice at one, two and four weeks post-TAC via echocardiography, organ index, morphology, and histology. At the end of the study, behavior and gene expression patterns were assessed, and overall survival was monitored. Compared to the sham-operated mice, ICR and C57BL/6J mice displayed hypertrophic phenotypes with a significant increase in ventricle wall thickness, heart weight and ratio, and cross-sectional area of cardiomyocytes after a 2-week TAC exposure. In addition, ICR mice developed reduced systolic function and severe lung congestion four weeks post-TAC, whereas C57BL/6J did not. Besides, ICR mice demonstrated comparable survival, similar gene expression alteration but severer fibrotic remodeling and poor behavioral performance compared to the C57BL/6J mice. Our data demonstrated that ICR was quite sensitive to TAC-induced heart failure and can be an ideal research tool to investigate mechanisms and drug intervention for pressure overload-induced HF.